2006
DOI: 10.1007/s00167-005-0698-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular stabilization after anterior cruciate ligament tear in children and adolescents: results 6 years after surgery

Abstract: Tear of the anterior cruciate ligament (ACL) secondary to knee sprain injury is also quite common among children and adolescents. Whether reconstruction is indicated and which technique should be employed is still controversial. The debate focuses on the possible risk of growth plate damages due to intraarticular operative reconstruction techniques. For more details on benefit and risks of operative stabilization, our clinic's large number of surgical results was to be evaluated retrospectively. In a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 43 publications
4
30
0
3
Order By: Relevance
“…[16][17][18][19] Arbes et al 16 reported on a mixed cohort of 63 patients, of whom only 20 were available for follow-up and only 3 underwent primary repair of the ACL. Of these 3 patients, 2 ultimately underwent ACL reconstruction.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…[16][17][18][19] Arbes et al 16 reported on a mixed cohort of 63 patients, of whom only 20 were available for follow-up and only 3 underwent primary repair of the ACL. Of these 3 patients, 2 ultimately underwent ACL reconstruction.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…A number of series' report transphyseal ACL reconstructions using a variety of grafts and fixation devices with good outcomes in pediatric patients and little risk of growth disturbance [8,10,[50][51][52][53][54][55], [56•], [57], [58•]. Aronowitz et al [50] used Achilles tendon allograft with 9-10 mm tunnels in patients with a skeletal age of at least 14.…”
Section: Transphyseal Techniquesmentioning
confidence: 99%
“…Gaulrapp et al [26], over a ten-year period (1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992), carried out 457 arthroscopies in children aged 3 to 16. They found 20% of ACL injuries, percentage similar to that found by Kellenberger and Von Laer [27].…”
Section: Therapeutic Managementmentioning
confidence: 99%